Social vs. Individual Centrality of Religiosity: Research in Religious and Non-Religious Settings in Russia - Prutskova, Elena (Religions, 2021)
Most of the current approaches to measuring religiosity operate with indicators of individual religiosity. One of the central ideas of the current paper is that religiosity is a social phenomenon. The Centrality of Religiosity Scale (CRS) developed by S. Huber is applied to measure the individual component of religiosity. A modification of the CRS (CRS-SOC) has been developed to include the social component of religiosity with two aspects: social connections with lay members of religious communities and with the clergy. The analysis is based on the data of two surveys conducted in Russia: an on-line survey with a general population sample (1768 respondents) and a survey of parishioners of four Christian denominations: Orthodox, Catholic, “traditional” Protestant (Lutheran, Baptist), and the “new” Protestant (Pentecostal) (1192 respondents). The structure of religiosity among parishioners of different Christian denominations is discussed. The results, which revealed that the level of religiosity among Orthodox parishioners is slightly lower, are interpreted using the theory of religious economy.